Regional anesthesia in neonates with cleft lip and palate: Retrospective study - Richtrová, Michaela; Košková, Olga; Janků, Martin; Bönischová, Tereza; Fabián, Dominik; Štourač, Petr (International journal of pediatric otorhinolaryngology, 2024)
BACKGROUND: Orofacial clefts are the most common congenital abnormalities. Cleft lip reconstruction is performed mostly in 3 months of life including the neonatal period. The consumption of opioids during anesthesia is one of the monitored parameters of anesthesia safety. We investigated the effect of using an infraorbital nerve block for reducing opioid consumption during cleft lip surgery in neonates. PATIENTS/METHODS: Overall, 100 patients who underwent primary cleft lip surgery in neonatal age between 2018 and 2021 were included in the study. The primary outcome was to compare opioid requirements during cleft lip surgery with and without using regional anesthesia. Secondary outcomes included a first oral intake from surgery between neonates with and without regional anesthesia and complications rate of infraorbital nerve block. RESULTS: Data from 100 patients (46 patients with and 64 without regional anesthesia) were retrospectively analyzed and classified into two groups according to whether regional anesthesia during neonatal cleft lip surgery had been performed or not. The use of infraorbital block was found to be positively correlated with lower doses of opioids used during the general anesthesia for the surgery (mean 0.48 μg/kg vs 0.29 μg/kg, p < 0.05). The postoperative course was evaluated based on the interval from surgery to first oral intake which was statistically insignificant shorter (p = 0.16) in the group of patients using regional anesthesia. No complications were recorded in the group of patients with regional anesthesia. CONCLUSIONS: Regional anesthesia is associated with reduced opioid consumption during anesthesia thereby increasing the safety of anesthesia in neonates. GOV IDENTIFIER: NCT06067854https://clinicaltrials.gov/study/NCT06067854?cond=NCT06067854&rank=1.
Keywords: Infant, Newborn; Cleft Palate; mužské pohlaví; Retrospective Studies; Male; retrospektivní studie; Female; Humans; Cleft Lip; novorozenec; pooperační bolest; Nerve Block; zákroky plastické chirurgie; lidé; ženské pohlaví; Anesthesia, Conduction; nervová blokáda; opioidní analgetika; rozštěp rtu; Analgesics, Opioid; rozštěp patra; Pain, Postoperative; svodná anestezie; Plastic Surgery Procedures